Sosialisasi Peran Artificial Intelligence (AI) dalam Proses Pembelajaran di Era Digital: Pengabdian - Nurmala; Nurhasanah; Nadrah Sitorus; Oknita; Kamaruzzaman; Ismuhar; Muhammad Saleh; Mudawali (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The development of AI technology has brought significant innovation to the world of education, simplifying activities and supporting the learning process. However, the adoption of AI in schools is hampered by suboptimal teacher skills, limited technological facilities, funding, human resources, and internet access. As a result, many teachers are less responsive to the use of technology, even though school administration is now shifting to online systems and communication technology contributes significantly to education. Therefore, it is crucial to conduct outreach at SMK Negeri 1 Nisam, North Aceh. The aim of the outreach is to provide understanding and education regarding the use of AI in the learning process in the digital era for participants consisting of teachers at SMK Negeri 1 Nisam, North Aceh through outreach activities. In this outreach activity, there is also direct practice in the use of several AI applications so that participants can utilize them in the future learning process. This activity was carried out independently and in collaboration between Lecturers from Esa Unggul University, Lecturers from STAI Ar-Ridho Bagansiapiapi, Lecturers from UIN Sultanah Nahrasiyah Lhokseumawe and students. The outreach included a site survey, problem identification, direct education, and evaluation at SMK Negeri 1 Nisam, North Aceh Regency.